Cloning, Gene Expression Analysis, and Phylogenic Relationship of dbat Gene from Iranian Endemic Yew (Taxus baccata L.) - M Majidi; M Farsi; AR Bahrami; J Behravan; SH Marashi (Institue of Medicinal Plants, ACECR, 2013)
Background: Taxol is one of the most important anticancer agents that its supply mainly depends on biological processes. 10 - deacetyl baccatin III- O- acetyl transferase (dbat) gene is one of the key genes in Taxol biosynthetic pathway and it is expected that overexpression of this gene would result in an increased production of taxol in biological systems. Objective: Investigation of dbat gene characteristics from Iranian endemic yew, Gene expression analysis and Construction of overexpression vector for this gene. Methods: First, sequence of the gene was cloned and then, sequence characteristics identified with Bioinformatics analysis. Gene expression analysis was performed under methyl jasmonate elicitation in several time-courses. Finally in order to construct overexpression vector, the sequence was cloned under the control of the CaMV35S promoter in to pCAMBIA1304. Results: Comparison of sequence similarities indicated that this sequence is most similar to Taxus × hunnewelliana. There was one unique amino acid substitution and investigating substituted amino acid revealed that, this replacement can not change overall characteristics of the enzyme and thus it would result in a functional enzyme. Analysis of gene expression showed that in response to methyl jasmonate, gene expression levels increased to maximum rate up to 24 times at 12 hours after elicitation. Finally gene insertion in suitable site of overexpression vector, confirmed by digest with restriction enzymes. Conclusion: Elicitation of shoot cuttings of Taxus would be a suitable alternative for Taxus cell cultures in gene expression analysis. Simplicity, feasibility, and deletion of time-consuming processes of cell culture are its main advantages.